Boundary Upwelling of Antarctic Bottom Water by Topographic Turbulence - Baker, LE; Mashayek, A; Naveira Garabato, AC (American Geophysical Union (AGU), 2023)
Publication status: Published Abstract The lower cell of the meridional overturning circulation (MOC) is sourced by dense Antarctic Bottom Waters (AABWs), which form and sink around Antarctica and subsequently fill the abyssal ocean. For the MOC to “overturn,” these dense waters must upwell via mixing with lighter waters above. Here, we investigate the processes underpinning such mixing, and the resulting water mass transformation, using an observationally forced, high‐resolution numerical model of the Drake Passage in the Southern Ocean. In the Drake Passage, the mixing of dense AABW formed in the Weddell Sea with lighter deep waters transported from the Pacific Ocean by the Antarctic Circumpolar Current is catalyzed by energetic flows impinging on rough topography. We find that multiple topographic interaction processes facilitate the mixing of the two water masses, ultimately resulting in the upwelling of waters with neutral density greater than 28.19 kg m −3 , and the downwelling of the lighter waters above. In particular, we identify the role of sharp density interfaces between AABW and overlying waters and find that the dynamics of the interfaces' interaction with topography can modify many of the processes that generate mixing. Such sharp interfaces between water masses have been observed in several parts of the global ocean, but are unresolved and unrepresented in climate‐scale ocean models. We suggest that they are likely to play an important role in abyssal dynamics and mixing, and therefore require further exploration.